Study on Heat Island Effect Induced by Land Use Change Increased Temperature in Metropolitan Jakarta - Sopia Lestari; Setyo S. Moersidik; Fadli Syamsudin (Institute for Research and Community Services (LPPM) ITB, 2015)
The heat island (HI) effect in metropolitan Jakarta was studied using air temperature measurements at 9 meteorological stations in Jakarta, Tanjung Priok, Serang, Halim, Cengkareng, Pondok Betung, Curug, Bogor, Citeko during 1986-2008 and Serpong during 2008-2011 and 2013; land use for forest, industry, water, settlement, open/cleared land in 1997, 2004, 2009, 2012; and total number of industries and total number of vehicles during 1986-2011. Harmonic analysis was used to remove the seasonal component from the temperature time series data, which was filtered with the 30-day moving average technique to capture trends whose significance was tested with the Mann-Kendall method. The results show that industry was a major factor in land use change over Jakarta with an increasing growth/year of 502 ha (9.76%) concentrated in the eastern part of Jakarta from 1997 to 2012. Industry had a spatial cover change similar to deforestation and open/cleared land expansion, especially in Jakarta from 2009 to 2012: 38.8%/year (industry), 8.3%/year(deforestation), and 13.8%/year (open/cleared land). The HI effect increased the temperature trend rate/year in Jakarta, Tanjung Priok, Serang, Halim, Pondok Betung, Cengkareng, Curug, and Bogor about 0.051°C, 0.021°C, 0.018°C, 0.012°C, 0.006°C, 0.006°C, 0.005°C, and 0.004°C from 1986 to 2008, respectively, equivalent to average warming in the city, suburban, and mountainous areas of around 2.5°C, 0.6°C, and 0.4°C, respectively within 100 years from 2009.